2018
DOI: 10.5109/1936211
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Glucomannan-Alginate as Vitamin C Excipient

Abstract: This work investigated the physicochemical properties of glucomannan-alginate combination as an excipient of vitamin C encapsulation. The effects of glucomannan-alginate ratio, concentration of vitamin C and preparation method on the encapsulation physicochemical properties were studied. Swelling and solubility of the vitamin C encapsulation were determined in 2 pH conditions which mimic the environment pH of the stomach and the lower gastrointestinal tract. The ratio of glucomannan-alginate on swelling at bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…1 shows changing the ratio of the matrix impacted to the efficiency. Changing the ratio of the excipient created different viscosities of the excipient, as also reported by Wardhani et al [18]. Variation in viscosity could affect the gel formation of the excipients which in turn influences the size of the bead as well as the capability of the matrix to entrap the vitamin.…”
Section: Entrapment Efficiencysupporting
confidence: 57%
See 1 more Smart Citation
“…1 shows changing the ratio of the matrix impacted to the efficiency. Changing the ratio of the excipient created different viscosities of the excipient, as also reported by Wardhani et al [18]. Variation in viscosity could affect the gel formation of the excipients which in turn influences the size of the bead as well as the capability of the matrix to entrap the vitamin.…”
Section: Entrapment Efficiencysupporting
confidence: 57%
“…This highest in efficiency could be in relation with its viscosity. Wardhani et al [18] reported this 3:1 ratio of glucomannan-alginate has the highest viscosity compare to other ratios.…”
Section: Entrapment Efficiencymentioning
confidence: 89%
“…Swelling power characterizes the developing power of a material; here, this refers to the ability of flour to expand. Swelling occurs because of the increase in the volume and the maximum weight of starch in water (Daramola & Osanyinlusi, 2006; Wardhani et al., 2018). Figures 4–6 illustrate the effects of dryer temperature in the hydrolysis, esterification, and ethanol methods using a UV rotary dryer with different rotational speeds and an oven dryer on the swelling power.…”
Section: Resultsmentioning
confidence: 99%
“…The swelling and water solubility of samples were measured based on the test described by Wardhani et al. (2018), with modifications. The baking expansion was determined as demonstrated by Demiate et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation